Pelatihan Pembuatan Linen Rumah Tangga dengan Menggunakan Teknik Ecoprint di Desa Kalobba Kabupaten Sinjai - Kurniati; Irmayanti; Andi Khaerun Niza; Fitry Purnamasari (Sakura Digital Nusantara, 2024)
Ecoprint is a coloring technique that uses plants in the environment such as leaves, flowers and other part of plants. This community service conducted in Kalobba Village, Tellulimpoe, Sinjai, South Sulawesi with the target of this activity was the housewives on that village. The aim of this activity is to improve community skills in making household linen using ecoprint techniques. The methods used in implementing this community service include: Lecture and demonstration methods. The activities began with a basic theory socialization activity regarding ecoprint training. The method of delivering training material adapts to the goals to be achieved, such as increasing knowledge, skills and forming attitudes is a strategy for implementing the training. Training participants gain knowledge about the potential of the surrounding environment, such as plants as natural dyes, knowledge about mordants and the ecoprint process and its fixation. Community service activities received a very good response from participants and the local government. For further development, it is hoped that the community can utilize the surrounding natural potential which has commercial value and economic value so that it can improve the people's standard living and reduce the unemployment rate.